No evidence for association between tau gene haplotypic variants and susceptibility to Creutzfeldt-Jakob disease - Sánchez-Juan, Pascual (BioMed Central, 2007)
BACKGROUND: A polymorphism at codon 129 of the prion protein gene (PRNP) is the only well-known genetic risk factor for Creutzfeldt-Jakob disease (CJD). However, there is increasing evidence that other loci outside the PRNP open reading frame might play a role in CJD aetiology as well. METHODS: We studied tau protein gene (MAPT) haplotypic variations in a population of sporadic and variant CJD patients. We tested 6 MAPT haplotype tagging SNPs (htSNPs) in a Dutch population-based sample of sporadic CJD (sCJD) patients and a cognitively normal control group of similar age distribution. We genotyped the same polymorphisms in two other sample groups of sCJD cases from Italy and the UK. In addition, we compared MAPT haplotypes between sCJD and variant CJD (vCJD) patients. RESULTS: Single locus and haplotype analyses did not detect any significant difference between sCJD cases and controls. When we compared MAPT haplotypes between sCJD and variant CJD (vCJD) patients, we found that two of them were represented differently (H1f: 8% in sCJD versus 2% in vCJD; H1j:1% in sCJD versus 7% in vCJD). However, these two haplotypes were rare in both groups of patients, and taking the small sample sizes into account, we cannot exclude that the differences are due to chance. None of the p-values remained statistically significant after applying a multiple testing correction. CONCLUSION: Our study shows no evidence for an association between MAPT gene variations and sCJD, and some weak evidence for an association to vCJD.